Smokers' Characteristics Associated with Successful Smoking Cessation Undergoing Pharmacotherapy in Slovenia - Drešček Marko; Miroševič Špela; Rifel Janez; Orešković Stjepan; Švab Igor; Homar Vesna (Sciendo, 2024)
Tobacco use is a major global health problem, contributing to premature death and disability. In Slovenia, the prevalence of smoking is higher than the EU average, emphasizing the need for effective tobacco control measures. The aim of this study was to identify the characteristics of patients most likely to benefit from pharmacotherapy for smoking cessation.